Neuroprotective strategies in cardiac surgery: a survey among South African anaesthesiologists - Kumalo, Nthabiseng Jacqueline (University of the Witwatersrand, Johannesburg, 2023)
Background The occurrence of neurological injury and cognitive disorders post cardiac surgery is a known complication that is described in literature. Neuroprotective strategies utilised intraoperatively can significantly improve postoperative neurological outcomes. The current challenge is the lack of standardised practice and protocols for intraoperative neuroprotection during cardiac surgery. This study looks at some of the currently applied neuroprotection strategies by clinicians during cardiac surgery. Methods A cross sectional,descriptive, contextual study was conducted amongst cardiothoracic anaesthetists and registrars in South Africa. A google link survey of the questionnaire consisting of 15 questions and 2 comment sections was sent out. To adhere to the protection of personal information act (POPIA), the questionnaire was centrally distributed via administration by the Cardiac Anaesthesia Society of South Africa (CASSA) and the South African Society of Anaesthesia (SASA), to its members. A link was shared with the members of CASSA during the Joint Peri-Operative Cardiothoracic (JPC) Annual Congress on the 20th of November 2021, and with the SASA members on the weekly online communication platform for the month of February 2022. Results A total of 101 clinicians around South Africa, involved in administering anaesthesia to patients requiring cardiac surgery, participated in this questionnaire. There is lack of standardized care for neuroprotection during cardiac surgery and availability on the stroke rates in most institutions. TTE use was preferred for atheromatous plaque assessment with epiaortic scanning barely used. Conclusion There is lack of standardised guidelines for the anaesthetic management of this high-risk population in academic and private centres across South Africa. This finding exposes a niche to be further explored by researchers to come up with preventative or risk minimising protocols during conduction of anaesthesia during the cardiopulmonary bypass (CPB) period.
A research report submitted in the partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology to the Faculty of Health Science, School of Clinical Medicine, University of the Witwatersrand, Johannesburg 2023
Keywords: Cardiac anaesthesia; Neuroprotective strategies; Perioperative care; Anaesthesiologist; Registrar; UCTD; SDG-3: Good health and well-being